ER-bound PTP1B is targeted to newly forming cell-matrix adhesions - Hernandez, Mariana Vanesa (2006)
Here, we define the mechanism through which protein tyrosine phosphatase 1B (PTP1B) is targeted to cell-matrix adhesion sites. Green fluorescent protein (GFP)-labeled PTP1B bearing the substrate-trapping mutation D181A was found in punctate structures in lamellae. The puncta co-localized with focal adhesion kinase (FAK) and Src, and defined the distal tips of cell-matrix adhesion sites identified with paxillin and vinculin. PTP1B is largely associated with the external face of the endoplasmic reticulum (ER) and the puncta develop from ER projections over cell-matrix adhesion sites, a process dependent on microtubules. Deletion of the ER-targeting sequence resulted in cytosolic localization and altered the distribution of PTP1B at cell-matrix foci, whereas mutations disrupting interactions with Src homology 3 (SH3) domains, and the insulin and cadherin receptors had no effect. PTP1B recognizes substrates within forming adhesion foci as revealed by its preferential association with paxillin as opposed to zyxin-containing foci. Our results suggest that PTP1B targets to immature cell-matrix foci in newly forming lamellae by dynamic extensions of the ER and contributes to the maturation of these sites.